2018
DOI: 10.1097/mao.0000000000001805
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Obstructive Sleep Apnea (OSA) in Spontaneous Cerebrospinal Fluid (CSF) Leaks: A Prospective Cohort Study

Abstract: OSA is highly prevalent among patients with sCSF leaks. All patients with sCSF leaks should undergo formal PSG testing. Future studies are needed to determine the role of OSA in the development of sCSF leaks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 32 publications
2
37
3
Order By: Relevance
“…Since the extracranial zygoma thickness is unaffected in sCSF‐L patients, 3 sCSF‐L likely occur due to an intracranial process that causes isolated skull thinning independent of obesity 3 . Researchers hypothesize obesity‐related factors, such as idiopathic intracranial hypertension (IIH) and OSA, play a role in the intracranial process that results in the development of sCSF‐L 3,4,20–22 (Fig. 4).…”
Section: Discussionmentioning
confidence: 99%
“…Since the extracranial zygoma thickness is unaffected in sCSF‐L patients, 3 sCSF‐L likely occur due to an intracranial process that causes isolated skull thinning independent of obesity 3 . Researchers hypothesize obesity‐related factors, such as idiopathic intracranial hypertension (IIH) and OSA, play a role in the intracranial process that results in the development of sCSF‐L 3,4,20–22 (Fig. 4).…”
Section: Discussionmentioning
confidence: 99%
“…16,22 A recent prospective study found that the prevalence of OSA among patients with sCSF-L is 83%. 17 We investigated a cohort of patients who were obese, yet did not have sCSF-L, and discovered that patients with moderate to severe OSA have thinning of the squamous portion of the temporal bone and skull base compared with non-OSA patients, a relationship independent of age, BMI, sex, and multiple comorbidities. We also found that patients with sCSF-L had nearly 20% thinner calvaria than those without OSA, similar to previous studies showing a mean 22% thinning of the skull in patients with sCSF-L. 15 We used the thickness of the squamous temporal bone as a surrogate for global calvarial thickness because it is not feasible to measure the entire calvarium.…”
Section: Discussionmentioning
confidence: 99%
“…15 This suggests an intracranial process leads to skull thinning and the development of sCSF-L. 15 Elevated intracranial pressure (ICP) on a constant or transient basis has been postulated to lead to skull thinning over time. 10,11,13 Elevated ICP has been documented in some (approximately 36%) but not all patients with sCSF-L. 10 In addition, OSA is associated with transient spikes in ICP during apnea episodes 16 and the prevalence of OSA is 83% in patients with sCSF-L. 17 Our study aimed to determine if OSA is independently associated with skull thinning by investigating the radiologic skull base and calvaria findings in non-sCSF-L patients with and without OSA based on formal PSG testing. To our knowledge, no studies have established a connection between OSA and skull thinning.…”
mentioning
confidence: 99%
“…sCSF-L has been associated with thinning of the calvarium with no changes to extracranial bones and is linked with obesity and OSA. 63,64 In particular, the incidence of OSA in sCSF-L patients was reported to be 83.3% and patients with OSA have been shown to have a thinner mean calvaria. 63,64 This suggests that there might be an indirect link between OSA and chronic untreated IIH.…”
Section: Osa and Iihmentioning
confidence: 99%